2019
DOI: 10.1002/jcb.28860
|View full text |Cite
|
Sign up to set email alerts
|

Explore prognostic marker of colorectal cancer based on ceRNA network

Abstract: Colorectal cancer (CRC) is one of the most common malignant tumors in the world. With the deepening of peopleʼs understanding of CRC at the molecular level, the survival and prognosis of CRC have been significantly improved with the help of surgery, radiotherapy, and chemotherapy, molecular targeted biological therapy and early detection of diseases. The research of different disciplines and the development of multihistological analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…MiRNAs are potential for amending tumor cells behaviors due to abnormal gene profiles for mature and precursor sequences compared to normal tissues [7,8]. Consisting of different tumor stromal cells, abundant ncRNA and other cytokines, tumor microenvironment (TME) is the pivotal concern of identifying prognosisrelated markers [9,10]. In the past dozen years, miRNAs have been demonstrated to be closely associated with the occurrence, development and prognosis of different tumors [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are potential for amending tumor cells behaviors due to abnormal gene profiles for mature and precursor sequences compared to normal tissues [7,8]. Consisting of different tumor stromal cells, abundant ncRNA and other cytokines, tumor microenvironment (TME) is the pivotal concern of identifying prognosisrelated markers [9,10]. In the past dozen years, miRNAs have been demonstrated to be closely associated with the occurrence, development and prognosis of different tumors [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Careful assessing sensitive and novel biomarkers could monitor the progress and prognosis of carcinoma outcomes [5][6][7][8][9][10][11]. Based on alterations in these molecular or pathways, different assessment of biomarkers that give novel insights into bladder urothelial carcinoma mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, H3F3A, as a diagnostic biomarker in the present study, was also identified as a hub gene, and maybe as a promoter of CRC progression and metastasis. The ceRNA network played a critical role in the initiation and progression of CRC (Ke et al, 2019;Ma et al, 2020). In the present study, we further constructed ceRNA networks based on those key exosomal genes.…”
Section: Discussionmentioning
confidence: 93%